The Influence of Brand Equity and Service Quality on Purchase Decisions on Garuda Indonesia Airline Services - Sri Wahyuni; Aurika Praninta (Publindo Akademika, 2021)
Airlines business growth rapidly in Indonesia and makes all of the airlines service company try to compete to be the best. Quality of service has been a key on marketing topic. Branding is one of the interesting topics for study also because branding is a competitive strategy. The purpose of this study is to examine influence of brand equity and service quality of purchase decision of Garuda Indonesia airlines. The samples for the study were 110 people who already using Garuda Indonesia airlines service at least once. Method of data collection using online questionnaire by Google Forms with Likert Scale 1-10. The techniques of data analysis using Structural Equation Modeling (SEM) AMOS program version 21.0 to verify the causality of two research hypothesis. The result of this research indicates that there was no influence between brand equity and purchase decision. Moreover, the research also indicates there was no influence between service quality and purchase decision.